The ACT youth justice system 2011 : a report to the ACT Legislative Assembly - Australian Capital Territory. Human Rights Commission; Roy, Alasdair; Watchirs, Helen; Australian Capital Territory. Legislative Assembly (Canberra : ACT Human Rights Commission, 2011)
annotation pending.
"Authors: Alasdair Roy ... Helen Watchirs"--T.p. verso.
"July 2011"--T.p. verso.
Includes bibliographical references.
Available on the ACT Human Rights Commission website as at 26/8/2011
Keywords: Juvenile justice, Administration of -- Australian Capital Territory; Juvenile delinquency -- Australian Capital Territory; Law enforcement - Criminal law and procedure - Juvenile justice; Australian Capital Territory (ACT SI55-16); Australian